2004
DOI: 10.1094/mpmi.2004.17.3.283
|View full text |Cite
|
Sign up to set email alerts
|

A Rhizobium leguminosarum Lipopolysaccharide Lipid-A Mutant Induces Nitrogen-Fixing Nodules with Delayed and Defective Bacteroid Formation

Abstract: Lipopolysaccharides from pea-nodulating strain Rhizobium leguminosarum by. viciae 3841, as all other members of the family Rhizobiaceae with the possible exception of Azorhizobium caulinodans, contains a very long chain fatty acid; 27-hydroxyoctacosanoic acid (27OHC28:0) in its lipid A region. The exact function and importance of this residue, however, is not known. In this work, a previously constructed mutant, Rhizobium leguminosarum by. viciae 22, deficient in the fatty acid residue, was analyzed for its sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
1
3

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 50 publications
(54 citation statements)
references
References 37 publications
1
48
1
3
Order By: Relevance
“…Bacteroids of LPS mutants are abnormal (29)(30)(31). The lpsB mutant of S. meliloti was found to be more sensitive to antimicrobial peptides (30).…”
Section: Discussionmentioning
confidence: 99%
“…Bacteroids of LPS mutants are abnormal (29)(30)(31). The lpsB mutant of S. meliloti was found to be more sensitive to antimicrobial peptides (30).…”
Section: Discussionmentioning
confidence: 99%
“…In the case of indeterminate nodules, it is possible that the maintenance of single occupancy symbiosomes results from more intimate contact between the dividing bacterial cell and the PM, whereas the latter determinate process involves detachment of the bacterial and PM cell. In the former case, we have reported that an R. leguminosarum biovar viciae mutant that is defective in the synthesis of the very long fatty acid moiety of its lipid A is also defective in bacteroid formation, and results in multiple occupancy symbiosomes (52,53). It is important to investigate the characteristics of the surface polysaccharides of bacteroids in these and other symbiotic systems in order to be able to fully understand the mechanism of symbiosis.…”
Section: Discussionmentioning
confidence: 99%
“…Detailed microscopy studies on the development of nodules and bacteroids for each of these mutants is required to fully understand any possible symbiotic function of these GalA residues. These more detailed studies are needed particularly in view of the already published data showing that disruption of acpXL, the gene that encodes the acyl carrier protein required for the synthesis of the very long chain fatty acid that is present on the lipid A, also results in nitrogen-fixing nodules; however, microscopic examination showed that bacteroid formation was severely affected (31)(32)(33). This work is currently in progress for each of the rgt mutants and will be described in an additional manuscript.…”
Section: Tablementioning
confidence: 99%